2007
DOI: 10.1007/s10800-007-9383-4
|View full text |Cite
|
Sign up to set email alerts
|

A quartz crystal microbalance study of the kinetics of interaction of benzotriazole with copper

Abstract: The kinetics of interaction of benzotriazole (C 6 H 5 N 3 , BTAH) with the surface of copper in salt water were studied using an electrochemical quartz crystal microbalance and X-ray photoelectron spectroscopy (XPS). Upon injecting BTAH into the electrolyte, three regions appear in the time response of the microbalance. Region I (at short time of few minutes), exhibits rapid linear growth of mass with time, which is attributed to the formation of a protective Cu(I)BTA complex. Region II reveals attachment of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Comparing the initial potentials of the anodic peak in the presence (*-0.10 V) and absence (*0 V) of BTAH, it can be seen that the additive causes a shift of *100 mV in the positive direction. These findings indicate that adsorption of the additive and so the formation of Cu(I)BTA occurred, corroborating Kharafi et al [16]. Figure 2 shows a typical plot of the anodic to cathodic charge ratio (q a /q c ) against the switching potential, E k, during potentiodynamic experiments in the absence (j) and in the presence (m) of BTAH.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Comparing the initial potentials of the anodic peak in the presence (*-0.10 V) and absence (*0 V) of BTAH, it can be seen that the additive causes a shift of *100 mV in the positive direction. These findings indicate that adsorption of the additive and so the formation of Cu(I)BTA occurred, corroborating Kharafi et al [16]. Figure 2 shows a typical plot of the anodic to cathodic charge ratio (q a /q c ) against the switching potential, E k, during potentiodynamic experiments in the absence (j) and in the presence (m) of BTAH.…”
Section: Resultssupporting
confidence: 84%
“…The copper dissolution charge density in the presence of BTAH (218.75 mC cm -2 ) is lower than in its absence (543.75 mC cm -2 ), due to differences in nucleation potential, which is more negative in the presence of BTAH. Kharafi et al [16] attributed the remarkable efficiency with which BTAH inhibits the corrosion of copper to its adsorption on the surface (BTAH ? Cu = BTAH:Cu) and formation of a protective complex (BTAH ?…”
Section: Resultsmentioning
confidence: 99%
“…XPS examination showed that the intensity of the N1s peak increased with the time of immersion, indicating more BTAH on the surface. Based on these findings, Al-Kharafi and co-workers [42] suggested the formation of a duplex inhibitor film composed of an inner thin layer of Cu(I)BTA and an outer layer of physically adsorbed BTAH which increases in thickness with time and BTAH concentration. On the other hand, the quartz crystal immittance (QCI) technique was used to characterize the film acoustic resistance and the resonator parallel capacitance [40].…”
Section: Introductionmentioning
confidence: 96%
“…For example, in case of a fresh Cu electrode immersed in BTAH solution, the observed low breakdown potential (E b = 20 mV) could be substantially increased (up to E b = 800 mV) after CV pretreatment with lower scan rates resulted in lower values of E b . On the other hand, Al-Kharafi and co-workers [42] distinguished three regions in the time response of the microbalance upon injecting BTAH into the electrolyte. At short time of few minutes (1st region), a rapid linear growth of mass with time was observed which was attributed to the formation of a protective Cu(I)BTA complex.…”
Section: Introductionmentioning
confidence: 99%
“…Copper corrosion inhibition is the system that is studied most often [37][38][39][40][41][42]. G. Trabanelli et al [37], who studied the corrosion inhibition of copper by various heterocyclic compounds (BTA, 2,4-dimercapto-pyrimidine, 5-mercapto-1-phenyltetrazole, 1H-1,2,3-triazolo [4,5-b]pyridine) in 0.1 M NaCl concluded that "EQCM technique has a valuable part to play in the interpretation of corrosion and corrosion inhibition mechanisms".…”
Section: Adsorption Of Organic Cis On Metals From Neutral Aqueous Solmentioning
confidence: 99%